2006
DOI: 10.1099/mic.0.29175-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity of the mucABD locus in Pseudomonas aeruginosa isolates from patients with cystic fibrosis

Abstract: The mucA gene of the muc operon, which is instrumental in the control of the biosynthesis of the exopolysaccharide alginate, is a hotspot of mutation in Pseudomonas aeruginosa, a micro-organism that chronically colonizes the airways of individuals with cystic fibrosis (CF). The mucA, mucB and mucD genes were sequenced in nine environmental isolates from aquatic habitats, and in 37 P. aeruginosa strains isolated from 10 patients with CF, at onset or at a late stage of chronic airway colonization, in order to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 35 publications
3
97
0
Order By: Relevance
“…In agreement with previous studies (Boucher et al, 1997b;Yoon et al, 2006;Bragonzi et al, 2006), mutations in mucA were found to be the main mechanism of conversion to mucoidy. However, we were also able to identify loss-offunction mutations in mucB or mucD in some non-mucoid isolates with increased alginate production on PIA plates (type II) or after prolonged incubation (type IV).…”
Section: Mutation In Algtsupporting
confidence: 82%
See 3 more Smart Citations
“…In agreement with previous studies (Boucher et al, 1997b;Yoon et al, 2006;Bragonzi et al, 2006), mutations in mucA were found to be the main mechanism of conversion to mucoidy. However, we were also able to identify loss-offunction mutations in mucB or mucD in some non-mucoid isolates with increased alginate production on PIA plates (type II) or after prolonged incubation (type IV).…”
Section: Mutation In Algtsupporting
confidence: 82%
“…However, the same types of mutations were also found in unrelated clones from different geographical locations in Scandinavia, suggesting that these loci represent hot-spot regions for mutation in mucA. In addition, the mucA22 mutation was reported previously in several mucoid isolates from the USA, Europe and Australia (Boucher et al, 1997b;Bragonzi et al, 2006;Anthony et al, 2002). Isolates belonging to the Dk1, Dk2 and N clones showed several other types of mutations.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…More than 80% of the frameshift or nonsense mutations that give rise to a premature stop signal are clustered within the 100 bp stretch from nt 340-439 of the 585 bp of the mucA gene. The most common mucA22 allele is characterized by a single base pair deletion at position 430, and it accounts for 40% of all stop mutations (Bragonzi et al, 2006). We isolated a mucoid strain from a patient who suffered from repeated pulmonary infection, which contained a previously unreported mucA allele (designated mucA56) characterized by a deletion of bases 166 to 333, and its sequence in Genebank is AY608668.…”
mentioning
confidence: 99%